The effect of unilateral hand muscle contraction on frontal alpha asymmetry and inhibitory control in intrinsic reward contexts, a randomized controlled trial - Atakan M. Akil; Renáta Cserjési; Tamás Nagy; Zsolt Demetrovics; H. N. Alexander Logemann (Scientific Reports)
Abstract Challenged inhibitory control has been implicated in various disorders, including addiction. Previous research suggests that asymmetry of frontal brain activity, indexed by frontal alpha asymmetry (FAA), is associated with inhibitory control and could be a target for neuromodulatory intervention. Some evidence suggests that unilateral muscle contraction (UMC) can modulate FAA; however, experimental evidence is scarce. We conducted a randomized controlled trial, with 65 participants (Mage = 26.6; SD = 7.4), 37 of whom were females. We collected EEG data to calculate FAA and assessed inhibitory performance using the Stop Signal Task (SST) in neutral and intrinsic reward (palatable food) conditions, both before and after a unilateral left-hand muscle contraction task aimed at enhancing right relative to left frontal activity. We found a significant main effect of group on FAA. Specifically, UMC group was associated with higher right relative to left frontal activity, associated with resting state inhibitory activity. Event-related potential analyses revealed a significant dissociation between the stop N2 and stop P3 components as a function of time. More specifically, as time progressed, the stop N2 was enhanced, while the stop P3 was reduced. These results did not lead to observable changes in the behavioral index of stopping. In conclusion, UMC did not affect any behavioral and brain activity indices. There is some indication of a potential effect on FAA. However, this effect could reflect coincidental differences in trait FAA. Our findings provide new insights into the temporal dynamics of brain activity indices of inhibitory control.